Transformasi Pendidikan Islam pada Era Nabi Muhammad SAW: Sebuah Studi Historis dan Praktis - Maryati, Sulis; A Ubaidillah (Fahima, 2024)
This study aims to examine the history of Islamic education during the time of Prophet Muhammad SAW, which became the main foundation in the development of science and education in Islamic civilization. The specific purpose of this research is to understand the vision, mission, goals, curriculum, educational methods, facilities and infrastructure, and education financing at that time. The research method used is a literature study with qualitative descriptive analysis. Data were collected from a variety of reliable literary sources, including books, scholarly articles, and works by historians of Islamic education. The results showed that education during the time of the Prophet Muhammad SAW had a vision to produce a generation of believers, noble morals, and mastering science. The mission of education includes the dissemination of Islamic teachings, moral formation, and the intelligence of the people. The purpose of education includes the formation of people who have faith, noble character and are capable in social life. The educational curriculum focuses on teaching the Quran, hadith, morals, Arabic, history, and life skills. The educational methods used include lectures, questions and answers, discussions, parables, and examples. Educational facilities and infrastructure include mosques as educational centers, kuttab to learn to read and write, suffah as dormitories to explore religious knowledge, and stationery. Education financing comes from zakat, infaq, sadaqah, ghanimah, and donations from wealthy friends, which are managed transparently and responsibly. This research provides insight into how Islamic education during the time of Prophet Muhammad (PBUH) was developed and became an inspiration for the Islamic education system in the present and future.